The Servant Leadership Effect on Student Engagement Mediated by Student Motivation at "X" Christian Senior High School in Surabaya - Damiana Wiwik; Ricky Ricky; Zeplin Jiwa Husada Tarigan (Petra International Journal of Business Studies, 2023)
This study aims to determine the effect of Servant Leadership (Voluntary Subordination (VS), Authentic Self (AS), Covenantal Relationship (CR), Responsible morality (RM), Transcendental spirituality (TS), Transforming Influence (TI)) on teachers on Student Engagement (SE) mediated by Student Motivation (SM) at "X" Christian Senior High School in Surabaya. This research method is causal-comparative quantitative, and the research respondents are 201 students in the 11th grade of the science study program. Partial Least Square (SmartPLS) version 3.0 is the data analysis method. This indicated that VS significantly affected SE. Authentic Self significantly affected SE. CR didn't significantly affect SE. However, RM significantly affected SE, TS significantly affected SE, and TI significantly affected SE. The mediating variables:  VS, AS, CR, RM, TS, and TI. Furthermore, School management needs to improve their professional relations with students and develop themselves to bring positive changes to students, increasing SE in the learning process.